2007
DOI: 10.1055/s-2007-993200
|View full text |Cite
|
Sign up to set email alerts
|

Metastatic Brain Tumor Surgery Using Fluorescein Sodium: Technical Note

Abstract: As for the surgical treatment of glioma, the recent employment of fluorescence-guided resection using 5-aminolevulinic acid (5-ALA) or high-dose fluorescein sodium has increased the rate of radical tumor resection. On the other hand, there is no specific technique for metastatic brain tumor surgery. We have used a fluorescence-guided tumor resection procedure with the aid of high-dose fluorescein sodium in surgery for metastatic brain tumor. Fluorescein sodium has been used in 13 cases, and achieved effective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 0 publications
0
22
1
Order By: Relevance
“…Tumors detected on imaging findings are thus stained, with no tumor specificity. 9 In the present study we found no differences in staining intensity among the metastases of different types of primary cancer.…”
Section: Discussioncontrasting
confidence: 59%
See 1 more Smart Citation
“…Tumors detected on imaging findings are thus stained, with no tumor specificity. 9 In the present study we found no differences in staining intensity among the metastases of different types of primary cancer.…”
Section: Discussioncontrasting
confidence: 59%
“…Thus, to achieve further improvements in local control, we have assessed the use of fluorescence-guided surgery of metastatic brain tumors using fluorescein sodium. 9 2. Methods and patients…”
Section: Introductionmentioning
confidence: 99%
“…[1053707492] One study reported that gross total resection (GTR) of GBM was achieved in 84.4% of patients who received fluorescein compared with only 30.1% of patients who did not. [92] These results were reproduced in a prospective study;[53] however, it should be noted that both studies failed to show a significant survival benefit despite higher rates of GTR in patients who received fluorescein.…”
Section: Fluorescein Sodiummentioning
confidence: 99%
“…This small dose is 15% of the dose previously used for neoplastic and vascular applications. 3,5,9,15,22,24 We chose this dose based on our previous experience. We had decreased fluorescein dosing gradually from 200 mg in 25 increments for the previous 10 patients who harbored brain aneurysms.…”
Section: Technique For Fluorescence Angiographymentioning
confidence: 99%